Infaq In The Qur'an and Its Role in Economic Empowerment - Evan Hamzah Muchtar; Shofiah Tidjani (STES Islamic Village, 2022)
Infaq is something that is very interesting at this time to be discussed and developed in the world of muamalah, where infaq is part of ZISWAF. Infak is a very interesting instrument that is developed in an open public manner into a real movement in strengthening the existence of Islamic Economy itself. Therefore, the aim of this study to elaborate the concept of infaq based on Quranic view and to determine the role of infaq in empowerment of society, particularly to de economic development for the poor. Thematic interpretation is a method using an approach to current contemporary themes, which requires problem solving from verse reviews, munasabah verses, asbabun nuzul, interpretation of verses and hadiths related to Infaq friends and related to current problems and the best solution is sought. In the Qur'an itself, there are many verses that discuss infaq, but the author focuses on Surah Al-Furqan: 67 (Makkiyah) which relates to the ability of people to give infaq, letters to 2, namely Al-Baqarah: 167 (Makkiyah) relating to people who donate will get a reward both k in this world or in the hereafter, the third letter is Surah Al-Baqarah: 274 (Madaniyyah) which discusses giving infaq in secret. Here the author also discusses Adab and Ethics in giving because this is very important and there is the greatest wisdom for people who likes to donate. The finding of this study are: in the Qur’an Allah mentions several verses regarding the issue of infaq and the role of infaq in economic empowerment has a significant relation to the welfare of mustahik.